Case Report: A case of necrotizing sarcoid granulomatosis mimicking metastatic tumor - Dong, Lingjun; Fu, Linhai; Wei, Desheng; Yu, Guangmao (Frontiers in Oncology, 2025)
This article presents a case study of a patient with early-stage lung cancer who received comprehensive management at our institution throughout the entire clinical course. During follow-up, multiple progressively enlarging solid nodules were detected in the right lung and pleural cavity. Positron emission tomography-computed tomography (PET-CT) demonstrated increased fluorodeoxyglucose (FDG) uptake in these nodules, with a maximum standardized uptake value (SUVmax) of 3.568. Following a multidisciplinary team (MDT) discussion, surgical resection of the nodules was undertaken. Pathological examination confirmed the diagnosis of necrotizing sarcoid granulomatosis (NSG), with special staining and microbiological testing yielding negative results, thereby excluding infectious lesions and tumor metastasis. This case highlights the critical importance of distinguishing metastatic tumors from NSG when new intrapulmonary or pleural nodules appear post-lung cancer surgery. Surgical biopsy is demonstrated to be an effective modality for achieving a definitive diagnosis.